2018
DOI: 10.4103/ajps.ajps_113_16
|View full text |Cite
|
Sign up to set email alerts
|

Nephrectomy in children with wilms' tumor: 15 years of experience with “Tumor Delivery Technique”

Abstract: Background:The contemporary surgical approach to Wilms' tumors follows that used in adults with renal cell carcinomas, namely, early occlusion of the renal vessels and then removal of the kidney as an intact mass. For years, the surgical approach at our institution has been different, starting with blunt separation of the kidney from the surrounding tissues, followed by its delivery outside the abdominal cavity while it is only attached to the major blood vessels which are subsequently ligated. We aimed to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Thereafter, upon excluding the duplicates and applying the inclusion criteria, a total of 20 studies were retained. Thirteen of the included studies were retrospective cohort studies (12,15,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), whereas seven of the included studies were prospective cohort studies (44)(45)(46)(47)(48)(49)(50). Qualitative and quantitative data were then extracted from all the studies and summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thereafter, upon excluding the duplicates and applying the inclusion criteria, a total of 20 studies were retained. Thirteen of the included studies were retrospective cohort studies (12,15,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), whereas seven of the included studies were prospective cohort studies (44)(45)(46)(47)(48)(49)(50). Qualitative and quantitative data were then extracted from all the studies and summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The survival rate was compared in six studies. Here, 10 studies reported the survival rate of children operated with radical nephrectomy ( 12 , 37 40 , 43 45 , 47 , 50 ), whereas six studies reported the outcome after nephron sparing surgery ( 12 , 37 39 , 47 , 50 ). A mean survival rate of 90.6 ± 8.7% was reported in 4,623 children operated with radical nephrectomy during a mean follow-up of 5.9 ± 3.5 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations